Description of the last instar larva of Calicnemia eximia (Selys, 1863) (Odonata: Platycnemididae) from West Bengal, India - Dawn, Prosenjit (Zootaxa, 2019)
The final instar larva of Calicnemia eximia (Selys, 1863) is described for the first time from a grass-bed under a waterfall in Buxa Tiger Reserve, Dooars of Darjeeling Himalayas. The larva shows a semi terrestrial nature like other congeneres but is unique in having no premental setae and a longer labium. One C. miniata (Selys, 1886) larva was also collected from the same locality and is compared with the C. eximia larva here.